2021
DOI: 10.1111/josi.12484
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ own and parental expectations for cross‐group friendship in the context of societal inequalities

Abstract: This study investigated adolescents' expectations about friendships between peers from different socioeconomic status (SES) in Nepal. Overall, Nepalese adolescents (N = 389, M age = 14.08; grades: 7-10) attributed more negative intentions to high-SES than to low-SES peers and expected that parents of high-SES targets would disapprove of cross-group friendships, referencing social hierarchies and reputation. Expectation about parents of low-SES targets were that they would support cross-SES friendships, citing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Evidence from children’s evaluations of racial- and gender-based exclusion has shown that children who are members of social groups that are typically viewed as lower on a social-cultural hierarchy often evaluate exclusion more negatively than their higher status peers (Cooley et al, 2019; Grütter et al, in press; Mulvey, 2016). It is not yet known whether this pattern would extend to wealth group membership, however, as ingroup preference might also motivate both high- and low-wealth children to prefer inclusion of same-wealth peers.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from children’s evaluations of racial- and gender-based exclusion has shown that children who are members of social groups that are typically viewed as lower on a social-cultural hierarchy often evaluate exclusion more negatively than their higher status peers (Cooley et al, 2019; Grütter et al, in press; Mulvey, 2016). It is not yet known whether this pattern would extend to wealth group membership, however, as ingroup preference might also motivate both high- and low-wealth children to prefer inclusion of same-wealth peers.…”
Section: Discussionmentioning
confidence: 99%
“…In the first article in this section, Grütter et al. (2021) consider how the caste system of Nepal and the social hierarchies associated with it influence adolescents’ expectations for cross‐group friendship in a sample of 389 rural adolescents from grades 7 to 10. The paper introduces a lens that lays bare how caste operates a social category in Nepal that is perceived as ethnic but is inseparable from socioeconomic status and wealth.…”
Section: Organization Of This Issuementioning
confidence: 99%
“…This study is a first step in understanding how parent and peer messages influence children's predictions of inclusion in interracial and same‐race peer contexts. While investigating the likelihood of inclusion among children from different racial backgrounds reflects an important context in the United States, it is necessary to note that children's predictions may differ when considering peer encounters between other racial groups or ethnicities within the United States (e.g., interactions between Latinx and Asian American children), in other countries, or among other social groups like gender or wealth status (Grütter et al., 2021). Future research should extend this work to explore other comparisons and samples.…”
Section: Discussionmentioning
confidence: 99%